Analisis Faktor-Faktor Yang Berperan Dalam Membangun Minat Mahasiswa Untuk Berwirausaha (Studi Kasus Mahasiswa/i Fakultas Ekonomi Jurusan Manajemen Uiversitas Kristen Indonesia Paulus) - Sambara, Kordiana; Salim, Astrianita; Baele, Yezhykel; Allo, Yohanis Tasik (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2023)
This study aims to find out what factors influence the interest of Indonesian Christian University Paulus Indonesia Department of Management students in 2018 and 2019 to become entrepreneurs. This research was conducted with a qualitative descriptive method. Sources of data used in this study is primary and secondary data with data collection techniques in the form of interviews, documentation and observation or direct observation of the respondents obtained and then analyzed into a conclusion from the research process. From the results of this study it can be concluded that there are several factors that influence student interest in entrepreneurship.